We have to prove that the tangent is an odd function.
If the tangent is an odd function, the following condition should be satisfied:
![\tan(t)=-\tan(-t)](https://img.qammunity.org/2023/formulas/mathematics/college/9ymfbvaj0k565ap9z27oig252320vudska.png)
From the figure we can see that the tangent can be expressed as:
We can start then from tan(t) and will try to arrive to -tan(-t):
![\begin{gathered} \tan(t)=(\sin(t))/(cos(t))=(y)/(x) \\ \tan(t)=(-(-y))/(x)=(-\sin(-t))/(\cos(-t)) \\ \tan(t)=-(\sin(-t))/(\cos(-t)) \\ \tan(t)=-\tan(-t) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/lee1dd010vuerzhvd4eqgx94hmla3pkqvb.png)
We have arrived to the condition for odd functions, so we have just proved that the tangent function is an odd function.